Effect of SO 2 and SO 3 Exposure to Cu-CHA on Surface Nitrate and N 2 O Formation for NH 3 –SCR - Han, Joonsoo; Bjerregaard, Joachim D.; Grönbeck, Henrik; Creaser, Derek; Olsson, Louise (ACS Engineering Au, 2024)
We report effects of SO and SO exposure on ammonium nitrate (AN) and N O formation in Cu-CHA used for NH -SCR. First-principles calculations and several characterizations (ICP, BET, XRD, UV-vis-DRS) were applied to characterize the Cu-CHA material and speciation of sulfur species. The first-principles calculations demonstrate that the SO exposure results in both (bi)sulfite and (bi)sulfate whereas the SO exposure yields only (bi)sulfate. Furthermore, SOx adsorption on framework-bound dicopper species is shown to be favored with respect to adsorption onto framework-bound monocopper species. Temperature-programmed reduction with H shows two clear reduction states and larger sulfur uptake for the SO -exposed Cu-CHA compared to the SO -exposed counterpart. Temperature-programmed desorption of formed ammonium nitrate (AN) highlights a significant decrease in nitrate storage due to sulfur species interacting with copper sites in the form of ammonium/copper (bi)bisulfite/sulfate. Especially, highly stable sulfur species from SO exposure influence the NO -SCR chemistry by decreasing the N O selectivity during NH -SCR whereas an increased N O selectivity was observed for the SO -exposed Cu-CHA sample. This study provides fundamental insights into how SO and SO affect the N O formation during ammonium nitrate decomposition in NH -SCR applications, which is a very important topic for practical applications.